2012
DOI: 10.1289/ehp.1104236
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Differences in the Body Burden–Age Relationships of Bioaccumulating Contaminants Based on Population Cross Sections versus Individuals

Abstract: Background: Body burdens of persistent bioaccumulative contaminants estimated from the cross-sectional biomonitoring of human populations are often plotted against age. Such relationships have previously been assumed to reflect the role of age in bioaccumulation.Objectives: We used a mechanistic modeling approach to reproduce concentration-versus-age relationships and investigate factors that influence them.Method: CoZMoMAN is an environmental fate and human food chain bioaccumulation model that estimates time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 36 publications
3
62
0
Order By: Relevance
“…Although the PCB concentration is well correlated with the number of years an individual has worked at the company it should not be used in isolation as proof that occupational exposure has occurred. Higher PCB concentrations have been reported in older individuals as a result of accumulation of the more persistent congeners and exposure to higher historical background concentrations (Megson et al, 2013a;Quinn and Wania, 2012). There are also several physiological characteristics, such as body fat, serum albumin and age, that can Table 1 PCB concentrations and enantiomer fractions recorded in workers.…”
Section: Concentrations Of Pcbs In Workers At a Transformer Dismantlimentioning
confidence: 99%
“…Although the PCB concentration is well correlated with the number of years an individual has worked at the company it should not be used in isolation as proof that occupational exposure has occurred. Higher PCB concentrations have been reported in older individuals as a result of accumulation of the more persistent congeners and exposure to higher historical background concentrations (Megson et al, 2013a;Quinn and Wania, 2012). There are also several physiological characteristics, such as body fat, serum albumin and age, that can Table 1 PCB concentrations and enantiomer fractions recorded in workers.…”
Section: Concentrations Of Pcbs In Workers At a Transformer Dismantlimentioning
confidence: 99%
“…Elimination rates and their half-lives are often adjusted for the body burden – age relationship (cf. (Quinn and Wania 2012), but our EFA has shown that distinct dietary routines are also underlying factors that should be part of the regression model specification.…”
Section: Discussionmentioning
confidence: 92%
“…Confounders showing significant correlation (p<0.05) with menstrual cycle function endpoints were included with contaminant variables in regression analyses against endocrine endpoints. Age is a primary correlate of bio-accumulated POHs (Quinn and Wania, 2012), so using age as one of the confounders removes the age effect from the exposure variables incorporating these organic contaminants. Body mass index (BMI) was not included as a potential confounder because it was not significantly correlated with the selected reproductive endpoints.…”
Section: Methodsmentioning
confidence: 99%